Inhibition of SDF-1 receptors CXCR4 and CXCR7 attenuates acute pulmonary inflammation via the adenosine A2B-receptor on blood cells - Konrad, Franziska Magdalena; Meichssner, Nadine; Bury, Annette; Ngamsri, Kristian-Christos; Reutershan, Jorg (Cell Death & Disease, 2017)
Acute pulmonary inflammation is characterized by migration of polymorphonuclear neutrophils into the different compartments of the lung. Recent studies showed evidence that the chemokine stromal cell-derived factor (SDF)-1 and its receptors CXCR4 and CXCR7 influence migration of immune cells and their activity was linked to adenosine concentrations. We investigated the particular role of CXCR4-and CXCR7-inhibition and the potential link to the adenosine A2B-receptor, which plays an important anti-inflammatory role in the lung. After LPS-inhalation for 45 minutes, administration of the CXCR4-inhibitor (AMD3100) decreased transendothelial and transepithelial migration, whereas CXCR7-antagonism influenced epithelial migration exclusively. In A2B −/ − mice, no anti-inflammatory effects were detectible through either one of the agents. Using chimeric mice, we identified A2B on hematopoietic cells to be crucial for these anti-inflammatory effects of CXCR4/7-inhibition. Both inhibitors decreased TNFα, IL6, CXCL1 and CXCL2/3 levels in the bronchoalveolar lavage of wild type mice, while not influencing the chemokine release in A2B −/ − mice. Inflammation augmented the expression of both receptors and their inhibition increased A2B-levels upon inflammation. In vitro assays with human epithelium/endothelium confirmed our in vivo findings. During inflammation, inhibition of CXCR4-and CXCR7-receptors prevented microvascular permeability in wild type but not in A2B −/ − mice, highlighting the pivotal role of an active A2B-receptor in this setting. The combination of both inhibitors had a synergistic effect in preventing capillary leakage. In conclusion, we determined the pivotal role of CXCR4-and CXCR7-inhibition in acute pulmonary inflammation, which depended on A2B-receptor signalling.
CRIS-Team Scopus Importer:2022-11-17